Analyzing How Spiritual Intelligence Affecting Stress Coping in Stress Management - Anggara Wisesa; Irenne Irenne (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Garut, 2020)
The issue of stress is becoming more serious in today's disruption era in which management is urged to pay more attention since it affects individual and even more organizational performance. Failing to answer this issue would bring unwanted impacts to the organization. This issue is not relatively new, but the consequences it brings urge organizations to find new alternative ways to answer this issue. One answer is coming from the study of spirituality and Spiritual Intelligence. This paper tries to conceptualize how this Spiritual Intelligence plays as a predictive factor of Stress Coping and how an individual copes with stress. From the literature analysis, we assume that spiritual intelligence has a significant role in stress management, and we found that Spiritual Intelligence relates to stress Coping in which Stress Coping Resources become a mediating factor between both. Spiritual Intelligence relates to stress Coping through three factors in Stress Coping Resources: Self-Efficacy, Cognitive Resources, and Perceived Stress. Through its seven dimensions, Spiritual Intelligence helps people to boost their mental health condition that is a requirement in surviving stress.